Influence of light on carbon utilization in aerobic anoxygenic phototrophs - Hauruseu, Dzmitry; Koblížek, Michal (Applied and environmental microbiology, 2012)
Aerobic anoxygenic phototrophs contain photosynthetic reaction centers composed of bacteriochlorophyll. These organisms are photoheterotrophs, as they require organic carbon substrates for their growth whereas light-derived energy has only an auxiliary function. To establish the contribution of light energy to their metabolism, we grew the phototrophic strain Erythrobacter sp. NAP1 in a carbon-limited chemostat regimen on defined carbon sources (glutamate, pyruvate, acetate, and glucose) under conditions of different light intensities. When grown in a light-dark cycle, these bacteria accumulated 25% to 110% more biomass in terms of carbon than cultures grown in the dark. Cultures grown on glutamate accumulated the most biomass at moderate light intensities of 50 to 150 μmol m(-2) s(-1) but were inhibited at higher light intensities. In the case of pyruvate, we did not find any inhibition of growth by high irradiance. The extent of anaplerotic carbon fixation was detemined by radioactive bicarbonate incorporation assays. While the carboxylation activity provided 4% to 11% of the cellular carbon in the pyruvate-grown culture, in the glutamate-grown cells it provided only approximately 1% of the carbon. Additionally, we tested the effect of light on respiration and photosynthetic electron flow. With increasing light intensity, respiration decreased to approximately 25% of its dark value and was replaced by photophosphorylation. The additional energy from light allows the aerobic anoxygenic phototrophs to accumulate the supplied organic carbon which would otherwise be respired. The higher efficiency of organic carbon utilization may provide an important competitive advantage during growth under carbon-limited conditions.
Keywords: hydrogenuhličitany; Carbon Isotopes; světlo; aerobióza; Aerobiosis; Carbon Cycle; pyruváty; Sphingomonadaceae; fototrofní procesy; Culture Media; biomasa; Bicarbonates; Pyruvates; Light; Darkness; kultivační média; Isotope Labeling; Carbon; izotopové značení; Phototrophic Processes; koloběh uhlíku; transport elektronů; izotopy uhlíku; Biomass; uhlík; tma; Electron Transport